2018
DOI: 10.1177/1744806918778641
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric changes over the whole brain in caffeine-containing combination-analgesic-overuse headache

Abstract: ObjectiveTo investigate brain morphometric changes in medication-overuse headache with excessive intake of caffeine-containing combination analgesics.Materials and methodsWe recruited 32 medication-overuse headache patients overusing caffeine-containing combination analgesics and 26 normal controls with matched sex and age. Magnetic resonance T1-weighted images were processed by automatic volume algorithm of brain regions over the whole brain according to the neuromorphometrics template. We explored the volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Moreover, the connectivity between middle occipital gyrus and posterior thalamus correlated significantly with migraine frequency. A structural MRI study (59) further demonstrated that the gray matter volume of the middle occipital gyrus exhibited significant associations with migraine frequency and migraine duration of the patients with MWoA, which was consistent with our findings to some extent. These results implied that the structural and functional abnormalities of the occipital cortex, notably of the middle occipital cortex, were not only associated with the specific changes of migraine with aura but were also considered an important pathological feature of MWoA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the connectivity between middle occipital gyrus and posterior thalamus correlated significantly with migraine frequency. A structural MRI study (59) further demonstrated that the gray matter volume of the middle occipital gyrus exhibited significant associations with migraine frequency and migraine duration of the patients with MWoA, which was consistent with our findings to some extent. These results implied that the structural and functional abnormalities of the occipital cortex, notably of the middle occipital cortex, were not only associated with the specific changes of migraine with aura but were also considered an important pathological feature of MWoA.…”
Section: Discussionsupporting
confidence: 91%
“…Various studies have previously illustrated structural and functional alterations of the occipital cortex in patients with migraine (22,(53)(54)(55), which are generally thought to be associated with the aura phenomenon, especially visual aura (56). Interestingly, these significant structural and functional alterations of the occipital cortex were also observed in patients with MWoA (57)(58)(59)(60)(61)(62). For example, in our recent study (61), a strong positive dynamic connectivity within the visual cortex and the significantly negative dynamic connectivity between middle occipital gyrus and posterior thalamus were found in MWoA patients.…”
Section: Discussionmentioning
confidence: 93%
“…MOH patients demonstrated impaired general cognition as indicated by lowered MoCA scores, particularly in the domains of visuospatial and executive function, attention, and orientation. Altered volume in cerebellum and regions related to affection and cognitive processing (right lateral orbital gyrus), visual (left calcarine, bilateral middle occipital gyrus, right superior parietal lobe, optic chiasm), and auditory (right temporal transverse gyrus) perception was observed in MOH patients, 20 which could be a morphological basis of cognitive impairment in MOH. Besides, MOH patients possessed prolonged P3 latency and lowered P3 amplitude, which could provide electrophysiological evidence for cognitive impairment in MOH.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, increased regional homogeneity (ReHo) values in the right middle occipital gyrus were reported in patients with CTN ( 34 ). Patients with drug-induced headaches exhibited an increased volume of the bilateral middle occipital gyrus ( 38 ). Furthermore, patients with pain-related conditions had altered neuronal activity or structural functions in the middle occipital gyrus ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with drug-induced headaches exhibited an increased volume of the bilateral middle occipital gyrus ( 38 ). Furthermore, patients with pain-related conditions had altered neuronal activity or structural functions in the middle occipital gyrus ( 38 , 39 ). These results suggested that the middle occipital gyrus may participate in the processes leading to the perception of pain in patients with diabetic polyneuropathy.…”
Section: Discussionmentioning
confidence: 99%